A note of quantitative diagnosis of compound errors in trough concentration system. (15th July 2022) - Song, Jifeng; Wang, Haiyu; Liu, Kunhao; Zou, Lianglin; Wang, Kai; Su, Ying; Wang, Qian; Zou, Zubing
Highlights: Use the camera to shoot at different angles to obtain a complete flux profile. Inversion method of traversal combined operation based on simplified algorithm. Identify the types and values of the optical errors in the flux profile. Flux image-based diagnosis of the Gaussian slope, gravity deformation and align error. Abstract: In practice, there are multiple optical errors existing in parabolic trough concentrator, which respectively have a unique effect on the flux distribution on the wall of the absorber, causing it to deviate from the ideal operating condition. Diagnosis for multiple errors is difficult. The effect of combined optical errors on the flux distribution can be modelled using convolution operations. In this study, the flux patterns under multiple types of optical errors are traversed and combined, and the actual flux distribution profiles of the parabolic trough concentrator measured by a camera-based method are compared to identify the Gaussian slope error, gravity deformation error and alignment error of the concentrator. This indicates that it is feasible to invert the flux profile on the absorber wall and diagnose the types and values of the corresponding optical errors of the concentrator.